ISLAMISASI ILMU EKONOMI - IRFAN SAUQI BEIK (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2016)
Abstract. Islamization of Economics. Islamic doctrine teaches all areas of human life. How to extract economic principles in the Qur'an and hadith are the biggest challenge todays, and then makes it into a body of knowledge as well to build it into a theoretically and practically discipline that differ significantly from the schools of the existing the conventional economics. But the critique and issue come up those Islamic financial services only "follow" the conventional economics, so the scientific originality is often questionable. In the process of Islamization economy, which has been carried out, namely through the development of well-being and poverty measurement tool that is based on the concept with CIBEST Model. CIBEST Model is an effort to develop a welfare approach to poverty based on the conception that a tool to measure well-being and poverty are not solely based on purely material, but also spiritual approach. It is based on the concept of fulfillment, where the al-Qur’an and Hadith has outlined those basically human needs consists of two things, the material and spiritual needs.Abstrak. Islamisasi Ilmu Ekonomi. Islam merupakan ajaran yang mencakup seluruh bidang kehidupan. Tantangan terbesar saat ini adalah bagaimana mengekstraksi prinsip-prinsip ekonomi dalam Al-Qur’an dan hadits, kemudian menurunkannya menjadi sebuah body of knowledge sekaligus membangunnya menjadi sebuah disiplin ilmu yang secara teoritis dan praktis berbeda signifikan dengan mazhab-mazhab ilmu ekonomi konvensional yang ada. Namun muncul kritik bahwa ekonomi syariah hanya “mengekor” ekonomi konvensional semata, sehingga orisinalitas keilmuannya sering dipertanyakan. Dalam proses islamisasi ekonomi, yang telah dilakukan, yaitu melaui pengembangan alat ukur kesejahteraan dan kemiskinan yang didasarkan pada konsep syariah dengan Model CIBEST. Model CIBEST adalah upaya untuk mengembangkan pendekatan kesejahteraan kemiskinan yang didasarkan pada konsepsi bahwa alat untuk mengukur kesejahteraan dan kemiskinan tidak semata mata didasarkan pada material semata, namun juga pendekatan spiritual. Hal ini didasarkan pada konsep pemenuhan kebutuhan, dimana al-Quran dan Hadis telah menggariskan bahwa pada dasarnya kebutuhan manusia terdiri atas dua hal, yaitu kebutuhan material dan spiritual.